Kedudukan Resolusi Dewan Keamanan PBB Menurut Pasal 25 Piagam PBB - Makarawung, Julio Franco Jehovah; Waas, Richard Marsilio; Daties, Dyah Ridhul Airin (Balobe Law Journal, 2024)
Introductioan: UN Security Council Resolutions in the form of decisions of the UN Security Council relating to the preservation and/or restoration of global peace and security which can be implemented legally, are essentially a valid statement of international law mandated by the goals and principles of the UN as outlined in the UN charter.Purposes of the Research: To analyze and find out about the Position of UN Security Council Resolutions according to Article 25 of the UN Charter.  Methods of the Research: Normative legal research or library legal research is a process of finding legal rules, legal principles, and legal doctors to answer legal issues faced.Results of the Research: The decisions of the UN Security Council are based on Article 25 of the Charter, which is truly legally binding, even more so that it can conflict with the principles of international treaty law, namely the principle of Pacta Tertiis Nec Nocent Nec Prosunt because all these decisions can be binding on countries. Countries that are not members of the UN as stated in Article 2 paragraph (6) and Article 49 of the Charter. The position of the UN Security Council Resolution is binding not only on UN member states but also on non-UN member states as stated in Article 2 paragraph (6).